2021
DOI: 10.1186/s12199-021-00935-3
|View full text |Cite
|
Sign up to set email alerts
|

Examining geographical disparities in the incubation period of the COVID-19 infected cases in Shenzhen and Hefei, China

Abstract: Background Current studies on the COVID-19 depicted a general incubation period distribution and did not examine whether the incubation period distribution varies across patients living in different geographical locations with varying environmental attributes. Profiling the incubation distributions geographically help to determine the appropriate quarantine duration for different regions. Methods This retrospective study mainly applied big data ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We identified 5012 records through PubMed, EMBASE, and Science Direct database searches, and documented the study selection process in a flowchart and showed the total numbers of retrieved references and the numbers of included and excluded studies (Figure 1). Based on the inclusion and exclusion criteria, 142 articles (8112 patients) were selected for analysis …”
Section: Resultsmentioning
confidence: 99%
“…We identified 5012 records through PubMed, EMBASE, and Science Direct database searches, and documented the study selection process in a flowchart and showed the total numbers of retrieved references and the numbers of included and excluded studies (Figure 1). Based on the inclusion and exclusion criteria, 142 articles (8112 patients) were selected for analysis …”
Section: Resultsmentioning
confidence: 99%
“…Quality assessment (Additional file 1 : Table S4 [ 9 , 10 , 12 , 13 , 21 , 22 , 26 – 32 , 34 , 37 40 , 42 – 60 , 62 – 65 , 67 – 71 , 73 , 74 , 76 , 78 – 86 , 89 , 90 , 92 – 94 , 97 – 99 , 101 – 107 , 109 – 115 , 117 121 , 123 – 128 , 130 , 131 , 133 , 136 – 139 , 141 – 153 , 155 – 161 , 164 – 166 ]) indicated that 1 study provided a precise exposure window for cases and identification of the potential infector(s). Sixty-eight studies included a well-characterized cohort of individuals that were comparable with the population and provided precise estimates for the symptom onset window for themselves and their potential infector(s).…”
Section: Resultsmentioning
confidence: 99%
“…3 , Additional file 1 : Fig. S1 [ 9 , 12 , 21 , 26 , 28 , 30 – 32 , 34 , 38 – 40 , 42 , 43 , 47 , 51 , 52 , 58 60 , 62 , 63 , 65 , 67 , 70 , 73 , 74 , 76 , 78 , 80 , 81 , 83 , 85 , 86 , 92 , 97 , 98 , 103 – 107 , 109 – 115 , 117 – 119 , 130 , 131 , 133 , 136 – 139 , 142 , 143 , 155 , 156 , 165 , 166 ]). Two studies did not specify the Omicron subvariant, and their pooled mean was 3.29 days (95% CI: 2.98–3.59 days); by pooling the estimates of the Omicron subvariants, the mean incubation period was 3.63 days (95% CI: 3.25–4.02 days).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 2020 ) found that older subjects have longer median incubation period than younger subjects, and Xiao et al. ( 2021 ) suggested that the incubation period distribution is associated with the meteorological temperature of the area. A regression framework allows us to more precisely evaluate the incubation period distribution for given subpopulations.…”
Section: Introductionmentioning
confidence: 99%